Adhesive and Cohesive Strength in FeB/Fe2B Systems - Meneses-Amador, Alfonso (2018)
In this work, FeB/Fe2B systems were evaluated by the scratch test. The powder-pack boriding process was performed on the surface of AISI M2 steel. The mechanical parameters, such as yield stress and Young’s modulus of the boride layer, were obtained by the instrumented indentation technique. Residual stresses produced on the boride layer were estimated by using the x-ray diffraction (XRD) technique. The scratch test was performed in order to evaluate the cohesive/adhesive strength of the FeB/Fe2B coating. In addition, a numerical evaluation of the scratch test on boride layers was performed by the finite element method. Maximum principal stresses were related to the failure mechanisms observed by the experimental scratch test. Shear stresses at the interfaces of the FeB/Fe2B/substrate system were also evaluated. Finally, the results obtained provide essential information about the effect of the layer thickness, the residual stresses, and the resilience modulus on the cohesive/adhesive strength in FeB/Fe2B systems.